ANALISIS WACANA CERPEN “WARISAN” DALAM MAJALAH PANJEBAR SEMANGAT NO. 33 – 14 AGUSTUS 2021 FAJRIN DWI ARTIKA - Yuliastuti, Kinasih; Indrayanto, Bayu; Anisa, Ike (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
The short story in the Panjebar Spirit magazine entitled "Inheritance" tells about a family’s fight over inheritance. The conflict began when the mother died and left a will that divided the inheritance between her children. However, the will sparked tension between the beneficiaries. This story highlights family values and honesty in dealing with difficult situations. This story can inspire readers to consider family values and honesty in their daily lives. The short story in Panjebar Selamat magazine entitled "Warisan" by Fajrin Dwi Artika is analyzed in discourse studies using grammatical analysis and lexical analysis tools. The dominant grammatical aspect is reference, while the more dominant lexical aspect is repetition.